Morphoagronomic variability of native quinoa (Chenopodium quinoa Willd.) Chimborazo type in Ecuador - Castro-Albán, Hugo Alejandro; Castro-Gómez, Rosa del Pilar; Alvarado-Capó, Yelenys (Agronomía Mesoamericana, 2023)
Introduction. Quinoa (Chenopodium quinoa Willd.) is a strategic and important crop for food security and sovereignty. It is the only plant-based food that provides all essential amino acids. Its wide varietal diversity constitutes a valuable genetic resource, as it adapts to different agroecological conditions and is tolerant to frost, drought and salinity. Objective. To perform a morpho-agronomic characterization of native Chimborazo-type quinoa in Ecuador. Materials and Methods. The research was conducted in the province of Chimborazo, Colta canton, Sicalpa parish, Ocpote Tablarumi community in Ecuador between January and July 2021. Seeds from an Andean family that had selected and conserved them in all cultivation cycles for generations were used. The crop was established by continuous sowing at a rate of 12 kg/ha in a total plot area of 640 m2 (estimate to contain 10,240 plants). After the emergence, 100 randomly selected plants were marked and taken as basic units for the population characterization. Phenotypic descriptors established at international level were used, evaluating both qualitative (16) and quantitative (12) traits. Results. The results revealed phenotypic variability. Stem and streak color, panicle diameter, panicle length, and days to harvest were the characteristics that most contributed to the observed variability. Conclusions. The population of native Chimborazo-type quinoa evaluated through 100 individuals showed phenotypic variability in both quantitative and qualitative traits, with greater frequency observed in panicle diameter, panicle length, petiole length, plant height, leaf width, yield, and stem and streak color.